THE INFLUENCE OF GREEN MARKETING ON PURCHASING DECISIONS OF AQUA DRINKING WATER - Purnama, Denta; Sanusi, Boby Arkan; Mujito (OIKONOMIA: Journal of Economics and Management Science, 2024)
The reason of this consider is to find out how consumers' choices to purchase Water brand bottled drinking water (AMDK) are affected by green promoting. Clients who are mindful of bottled drinking water (AMDK) merchandise were inquired to take an interest within the overview in arrange to assemble information. Data analysis was done using SPSS software and statistical hypothesis testing. A questionnaire that was given to clients who were acquainted with bottled drinking water (AMDK) products was used to obtain primary data. Ad hoc sampling was used to get a sample size of one hundred individuals.The findings demonstrate a definite positive correlation between green marketing and consumer choice. The knowledge gathered from this study will enable anyone considering utilizing bottled water products to make wise decisions that will significantly enhance their